1989
DOI: 10.1149/1.2096635
|View full text |Cite
|
Sign up to set email alerts
|

Surface Chemistry of Sputter‐Deposited Al‐Mo and Al‐Cr Alloys Polarized in 0.1N   KCl

Abstract: A study was performed to investigate the changes that take place in the chemistry of the passive film that forms on A1 alloys containing either Mo or Cr, as a function of solute concentration and applied potential in 0.1N KC1. The results show that the mechanisms by which the solute protects the Al alloy differ. Molybdenum forms a film containing MoO4 -2 that impedes the ingress and movement of the C1-anion in the film. In contrast, Cr forms a CrOOH barrier layer that inhibits the oxidation of the A1 substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 20 publications
4
61
0
Order By: Relevance
“…Several different mechanisms have been proposed to explain the passivity of stainless aluminum alloys, including electrostatic repulsion of Cl" by oxidized solute atoms [1][2][3], formation of an oxidized solute barrier layer [3,4], blockage of Cl" transport through the passive film [22], stabilization of the passive film oxide structure [6], replacement of oxidized Al in the passive film by oxidized solute to form a more stable oxide [28,29], reduction of the critical pH for pit propagation [17][18][19][20], and reduction in C1-adsorption due to pHpzc changes [11][12][13][14][15]. Additionally, Macdonald and coworkers [34,35] studying Mo-and W-containing stainless steels have proposed a solutevacancy interaction model (SVIM).…”
Section: Passivity Mechanism Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Several different mechanisms have been proposed to explain the passivity of stainless aluminum alloys, including electrostatic repulsion of Cl" by oxidized solute atoms [1][2][3], formation of an oxidized solute barrier layer [3,4], blockage of Cl" transport through the passive film [22], stabilization of the passive film oxide structure [6], replacement of oxidized Al in the passive film by oxidized solute to form a more stable oxide [28,29], reduction of the critical pH for pit propagation [17][18][19][20], and reduction in C1-adsorption due to pHpzc changes [11][12][13][14][15]. Additionally, Macdonald and coworkers [34,35] studying Mo-and W-containing stainless steels have proposed a solutevacancy interaction model (SVIM).…”
Section: Passivity Mechanism Backgroundmentioning
confidence: 99%
“…In the last several years, supersaturated aluminum alloys with Mo, Cr, Ta, W, Zr, Nb, Zn, V, Cu, Ti, and Si have been produced by several groups using rapid solidification or other nonequilibrium methods , such as sputter deposition [1][2][3][4][5][6][7][8][9][10][16][17][18][19][20][21][22][23][28][29][30][31][32][33], ion implantation [11][12][13][14][15]24,25], melt spinning [27], and vapor deposition [26,33]. Several alloys have shown significant improvements in passivity in chloridecontaining environments.…”
Section: Introductionmentioning
confidence: 99%
“…Also, some samples display superconducting behavior with surprisingly critical temperature (T C ) as high as 10 K 8 . Additionally, molybdates have attracted great attention due to the existence of many valences of the Mo ions (from 2+ to 6+) 9 . Recently, the study of the Mo valences in the Li 0.9 Mo 6 O 17 compound unambiguously showed an interesting connection with the formation of 1D channels in this compound 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Anderson et al studied the corrosion behavior of the sputter-deposited amorphous Ni-Nb coatings on commercial 316L stainless steel in different aggressive media and they found that the amorphous Ni-Nb coatings have good corrosion resistance [10]. It has been reported that the alloying of niobium with copper [11], aluminum [12], chromium [13], molybdenum [14] and magnesium [15] enhances the protective quality of the passive films in aggressive media. The sputter-deposited Cu-Nb [11], Al-Nb [12] and Mg-Nb [15] alloys were spontaneously passivated and showed high corrosion resistance in aggressive media even though these alloys did not show higher corrosion resistance than those of alloy−constituting elements.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the alloying of niobium with copper [11], aluminum [12], chromium [13], molybdenum [14] and magnesium [15] enhances the protective quality of the passive films in aggressive media. The sputter-deposited Cu-Nb [11], Al-Nb [12] and Mg-Nb [15] alloys were spontaneously passivated and showed high corrosion resistance in aggressive media even though these alloys did not show higher corrosion resistance than those of alloy−constituting elements. However, the most interesting fact has been reported, during last two decades, that the corrosion rates of the sputter-deposited Cr-Nb [13,16,17] and Mo-Nb [14,17] alloys were lower than those of alloy constituting elements due to the spontaneous passivation in aggressive HCl solutions.…”
Section: Introductionmentioning
confidence: 99%